Accuracy of sonographic fetal weight estimation in a tertiary care hospital in Bharatpur, Nepal - Prasad, V Natraj; Poudel, Pratik; Chhetry, Pramod Kumar (Journal of College of Medical Sciences-Nepal, 2017)
Background & Objectives: Among the various methods used in the estimation of intrauterine fetal weight, sonographic fetal weight estimation is the one and has become an important component of antenatal care. The study was conducted with objective to assess the accuracy and reliability of ultrasound estimation of fetal weight in women with a singleton term pregnancy. Materials & Methods: This was a prospective cross-sectional study of 120 women with singleton term pregnancies. Ultrasound estimated fetal weight was calculated by measuring the biparietal diameter and abdominal circumference. The estimated fetal weight was compared to the actual birth weight post delivery. The correlation between estimated fetal weight and actual birth weight was assessed by Pearson’s correlation coefficient and the accuracy of sonographic fetal weight estimation was measured using mean error, mean absolute error, mean percentage error, mean absolute percentage error and proportion of estimates within 10% of actual birth weight. Results were tested at error level set at p ≤ 0.05. Results: Mean estimated and actual birth weights were 2863.5 ± 441.9 g and 2822.5 ± 407.7 g respectively. There was a strong positive correlation between estimated fetal weight and actual birth weight (r= 0.71, p <0.001). The mean percentage error and mean absolute percentage error of ultrasound fetal weight estimations were 1.9 ± 11.4% and 8.8 ± 7.5% respectively. Conclusion: Sonographically estimated fetal weight had strong positive correlation with actual birth weight and thus sonography can be used in the estimation of fetal weight for the better perinatal outcome.